Money and finance after the crisis : critical thinking for uncertain times - Christophers, Brett, 1971-; Leyshon, Andrew; Mann, Geoff (Online access with DDA: Askews (Economics), 2017)
Money and Finance After the Crisis provides a critical multi-disciplinary perspective on the post-crisis financial world in all its complexity, dynamism and unpredictability. Contributions illuminate the diversity of ways in which money and finance continue to shape global political economy and society.-A multidisciplinary collection of essays that study the geographies of money and finance that have unfolded in the wake of the financial crisis -Contributions discuss a wide range of contemporary social formations, including the complexities of modern debt-driven financial markets -Chapters critically explore proliferating forms and spaces of financial power, from the realms of orthodox finance capital to biodiversity conservation -Contributions demonstrate the centrality of money and finance to contemporary capitalism and its political and cultural economies.